DEFOLIATING INSECTS IMPACTS ON FOREST ECOSYSTEMS - Cristina STANCĂ-MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The impact on forest ecosystems caused by insect has two components, one ecological and one socio-economical. Ecological component relates to the effects of environmental parameters overview of the stands, with direct results in time on individual trees, as on the other components of ecosystems. The socio-economical component of the impact shows how these effects influence the forest resources including the productive ones and the aesthetic recreational ones. While the socio-economic value is expressed in units of currency/unit area (euro/ha), the environmental impact can be expressed in terms like: modifying the composition stands, reducing density, reducing annual growth rate or period etc. Each of these two components of the impact can be treated after the effect of time on the ecosystem, namely: long or short. At the level of forest ecosystems, with a complexity and objectives of management different, the concept of short or long term, is quite relative, so that below will not be explicit reference to the mode of action in time of the defoliators effects but only on each component of the forest ecosystem.